Integrating Teaching with Other Aspects of Professorial Work: A Comparison of Experienced and Inexperienced Faculty’s Role Conceptualizations - Kreber, Carolin (Canadian Journal of Higher Education, 2000)
This article reports on a study which investigated the extent to which experienced and inexperienced faculty at Canadian universities integrate their various professorial roles. How faculty conceptualize their work was explored from the perspective of Kelly’s (1955) personal construct theory. Experienced faculty were found to integrate the various roles associated with professorial work more strongly than inexperienced faculty. Furthermore, when all activities associated with the teaching role were considered as a single variable, experienced faculty were found to integrate the teaching function more strongly with research and service activities than did their inexperienced peers. Further comparative analyses focussing on specific professorial activities revealed that the two groups showed the highest level of agreement in how they conceptualized the research role, but the highest level of disagreement in how they conceptualized the teaching role. The results of this repertory grid study are discussed in relation to the present culture of higher education that espouses integration of faculty roles as a goal, but at the same time allows only for little opportunity for new faculty to develop the ability to integrate. Some suggestions for the practice of faculty development are offered.